Effects of Climate Change and Various Grassland Management Practices on Grasshopper (Orthoptera) Assemblages. (2nd July 2014) - Kenyeres, Zoltán; Cservenka, Judit
Abstract : Influence of different grassland management practices on Orthoptera assemblages inhabiting humid grassland areas was studied since 2003 to 2011. The examined sites were within the protected area of Balaton Uplands National Park. The physiognomy and climatic conditions of the studied habitats were similar but their land use types were significantly different. After the preliminary analyses of Nonmetric multidimensional scaling, neighbour joining clustering, and Spearman rank correlation, we examined the possible effects of such independent variables as land use (nonmanagement, mowing, grazing), microclimate (humidity and temperature), regional macroclimate (annual and monthly mean temperatures and rainfall), using General Linear Mixed Models, and canonical correlation analysis. Our results showed that the effect of grassland management practices on the organization of Orthoptera assemblages was at least as important as that of macro- and microclimate. Furthermore, grassland management could intensify the influence of several local and regional parameters. These results can help finding the most suitable type of grassland management to conserve the grasshopper assemblages.